Short Metaphyseal Femoral Stem Total Hip Arthroplasty in Poor Quality Bone Cortex Without Neck Length Sparing: A Case Report - Khamkhad, Aekkarith (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: The principle of short metaphyseal femoral stem total hip arthroplasty (short stem THA) required the cortical ring of the femoral neck and lateral touch of the distal stem at the proximal femur, but this case had an improper cortical ring of the femoral neck and lateral touch. Methods: A case report of a 39-year-old male who underwent short stem THA surgery owing to a failure of the femoral neck fixation and delayed union of the femoral shaft fracture. Results: The patient reported successful 5-year clinical and radiographic outcomes for a short stem THA. Conclusions: Short stem THA could be an alternative implant option, compared with conventional cementless stem, for young patients with good bone quality, despite lacking femoral neck anchoring, with superiority in terms of bone stock preservation and more natural loading.